2022
DOI: 10.1186/s40104-022-00792-2
|View full text |Cite
|
Sign up to set email alerts
|

Full-fat insect meals in ruminant nutrition: in vitro rumen fermentation characteristics and lipid biohydrogenation

Abstract: Background The most used protein sources in ruminant nutrition are considered as having negative impacts in terms of environmental sustainability and competition with human nutrition. Therefore, the investigation of alternative and sustainable feedstuffs is becoming a priority in ruminant production systems. Results This trial was designed to evaluate eight full-fat insect meals (Acheta domesticus – ACD; Alphitobius diaperinus – ALD; Blatta lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
1
8
0
1
Order By: Relevance
“…Ruminal degradation of SBM proteins has been well characterized, whereas information on protein fractions and protein degradation rate of insect meals is still very scant. Renna et al (2022b) observed lower ruminal ammonia content when comparing the use of various full-fat insect meals and plant meals, consistent with a previous comparison between H. illucens larvae meal and SBM ( Jayanegara et al, 2017a ). Such result would be advantageous in ruminant nutrition provided that intestinal digestibility of nondegraded protein in the rumen is high.…”
Section: Insect Meals As Protein-rich Feedstuffssupporting
confidence: 90%
See 3 more Smart Citations
“…Ruminal degradation of SBM proteins has been well characterized, whereas information on protein fractions and protein degradation rate of insect meals is still very scant. Renna et al (2022b) observed lower ruminal ammonia content when comparing the use of various full-fat insect meals and plant meals, consistent with a previous comparison between H. illucens larvae meal and SBM ( Jayanegara et al, 2017a ). Such result would be advantageous in ruminant nutrition provided that intestinal digestibility of nondegraded protein in the rumen is high.…”
Section: Insect Meals As Protein-rich Feedstuffssupporting
confidence: 90%
“…However, a subsequent study by the same research team showed that lowering the chitin content in Gryllus assimilis did not improve its overall digestibility characteristics ( Jayanegara et al, 2017b ), suggesting a minor role of chitin on overall digestibility. Renna et al (2022b) also found that B. lateralis had the highest chitin content among the tested full-fat insect meals, but it displayed the most promising results in terms of fermentation. These results would support that chitin is degradable to certain extent in the rumen ( Fadel El-Seed et al, 2003 ).…”
Section: Insect Meals As Protein-rich Feedstuffsmentioning
confidence: 86%
See 2 more Smart Citations
“…A relatively lower ammonia concentration was observed in an in vitro study where Gryllus bimaculatus was used at 25% inclusion instead of SBM [18]. However, different insect species can exhibit variable fermentation patterns in the rumen, as highlighted in a study with Blatta lateralis beetles, which produced more NH 3 -N [40]. This variation is attributed to differences in protein, fat, and chitin levels among insect species.…”
Section: Discussionmentioning
confidence: 92%